2022
DOI: 10.1111/pce.14509
|View full text |Cite
|
Sign up to set email alerts
|

The hot science in rice research: How rice plants cope with heat stress

Abstract: Global climate change has great impacts on plant growth and development, reducing crop productivity worldwide. Rice (Oryza sativa L.), one of the world's most important food crops, is susceptible to high-temperature stress from seedling stage to reproductive stage. In this review, we summarize recent advances in understanding the molecular mechanisms underlying heat stress responses in rice, including heat sensing and signalling, transcriptional regulation, transcript processing, protein translation, and post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 170 publications
0
31
0
Order By: Relevance
“…Enhancing heat stress tolerance in plants is crucial due to the detrimental effects of extreme temperatures on plant growth, development, and productivity (Lobell et al, 2011). Heat stress negatively impacts crop yield and quality, reducing photosynthesis, carbon assimilation, energy metabolism, and disrupting reproductive processes like flower formation and pollen viability (Li et al, 2023). Understanding the mechanisms underlying heat stress tolerance in plants is vital for developing strategies to improve thermotolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancing heat stress tolerance in plants is crucial due to the detrimental effects of extreme temperatures on plant growth, development, and productivity (Lobell et al, 2011). Heat stress negatively impacts crop yield and quality, reducing photosynthesis, carbon assimilation, energy metabolism, and disrupting reproductive processes like flower formation and pollen viability (Li et al, 2023). Understanding the mechanisms underlying heat stress tolerance in plants is vital for developing strategies to improve thermotolerance.…”
Section: Discussionmentioning
confidence: 99%
“…As stationary organisms, plants have developed various strategies to withstand changing environmental conditions (Ding et al, 2020). Numerous studies have demonstrated that plants are more vulnerable to heat stress during the reproductive stage compared with the vegetative stage (Ma et al, 2020; Chaturvedi et al, 2021; Li et al, 2023). However, the mechanisms by which plants adapt to heat stress during the reproductive stage are not well understood in relation to the vegetative stage.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of heat stress on rice production, quality, physiology, heat‐regulated genes and networks have been well summarized (Jagadish et al, 2015; Y. Yang, Yu, et al, 2022). Li et al (2023), in this issue, reviewed mainly recent advances in heat sensing and signalling, regulation of the heat stress response in rice, besides irreversible effects of heat stress on photosynthesis, reproduction, and quality in rice (J. Y. Li et al, 2023). The capacity of rice to balance heat stress response and growth, needs more attentions in future studies.…”
Section: Abiotic Resilience Of Ricementioning
confidence: 99%
“…Together, these thermosensors sense high temperatures in the environment and efficiently, repeatedly, and stably transmit heat signals to downstream response factors (Vu et al, 2019;Guihur et al, 2022). On the other hand, research into rice has mainly focused on the response to hightemperature stress in recent years, but it is well established that hightemperature stress can cause protein misfolding and accumulation of high levels of reactive oxygen species (ROS) in rice, which reduce plant thermotolerance (Li et al, 2022).…”
Section: Heat Stress Responses In Ricementioning
confidence: 99%